Development and validation of the Australian Aboriginal racial identity and self-esteem survey for 8-12 year old children (IRISE-C) - Kickett-Tucker, Cheryl; Christensen, D.; Lawrence, D.; Zubrick, S.; Johnson, D.; Stanley, F. (BioMed Central Ltd., 2015)
Introduction: In Australia, there is little empirical research of the racial identity of Indigenous children and youth as the majority of the current literature focuses on adults. Furthermore, there are no instruments developed with cultural appropriateness when exploring the identity and self-esteem of the Australian Aboriginal population, especially children. The IRISE-C (Racial Identity and Self-Esteem of children) inventory was developed to explore the elements of racial identity and self-esteem of urban, rural and regional Aboriginal children. This paper describes the development and validation of the IRISE-C instrument with over 250 Aboriginal children aged 8 to 12 years. Methods: A pilot of the IRISE C instrument was combined with individual interviews and was undertaken with 35 urban Aboriginal children aged 8-12 years. An exploratory factor analysis was performed to refine the survey and reduce redundant items in readiness for the main study. In the main study, the IRISE C was employed to 229 Aboriginal children aged 6-13 years across three sites (rural, regional and urban) in Western Australia. An exploratory factor analysis using Principal axis factoring was used to assess the fit of items and survey structure. A confirmatory factor analysis was then employed using LISREL (diagonally weighted least squares) to assess factor structures across domains. Internal consistency and reliability of subscales were assessed using Cronbach's co-efficient alpha. Results: The pilot testing identified two key concepts - children's knowledge of issues related to their racial identity, and the importance, or salience, that they attach to these issues. In the main study, factor analyses showed two clear factors relating to: Aboriginal culture and traditions; and a sense of belonging to an Aboriginal community. Principal Axis Factoring of the Knowledge items supported a 2-factor solution, which explained 38.7 % of variance. Factor One (Aboriginal culture) had a Cronbach's alpha of 0.835; Factor 2 (racial identity) had a Cronbach's alpha of 0.800, thus demonstrating high internal reliability of the scales. Conclusion: The IRISE-C has been shown to be a valid instrument useful of exploring the development of racial identity of Australian Aboriginal children across the 8-12 year old age range and across urban, rural and regional geographical locations.